A review of biophysical and socio-economic effects of unconventional oil and gas extraction – Implications for South Africa. (15th December 2016) - Esterhuyse, Surina; Avenant, Marinda; Redelinghuys, Nola; Kijko, Andrzej; Glazewski, Jan; Plit, Lisa; Kemp, Marthie; Smit, Ansie; Vos, A. Tascha; Williamson, Richard
Abstract: The impacts associated with unconventional oil and gas (UOG) extraction will be cumulative in nature and will most likely occur on a regional scale, highlighting the importance of using strategic decision-making and management tools. Managing possible impacts responsibly is extremely important in a water scarce country such as South Africa, versus countries where more water may be available for UOG extraction activities. This review article explains the possible biophysical and socio-economic impacts associated with UOG extraction within the South African context and how these complex impacts interlink. Relevant policy and governance frameworks to manage these impacts are also highlighted. Highlights: Unconventional oil and gas extraction impacts are cumulative and may occur on a regional scale. The nature of the impacts highlights the importance of using strategic environmental decision-making and management tools. Managing possible impacts responsibly is extremely important in a water scarce country such as South Africa. This review article explains the possible biophysical and socio-economic impacts within the South African context. Policy and governance frameworks to manage these impacts are also highlighted.